Protective effects of fulvotomentosides on acetaminophen-induced hepatotoxicity - Liu Ya-Ping; Liu Jie; Jia Xian-Sheng; Mao Qing; Madhu Cherukury; Klaassen Curtis D (Acta Pharmacologica Sinica; Vol 13, No 3 (May 1992): Acta Pharmacologica Sinica, 2016)
Fulvotomentosides (Ful) is the total saponins of Lonicera fulvotomentosa. In the present study, we examined the effect of Ful on acetaminophen (AA)-induced hepatotoxicity in mice. Ful pretreatment (75-225 mg.kg-1, sc x 3 d) significantly decreased AA (500 mg.kg-1, ip)-induced liver damage as indicated by serum activities of alanine aminotransferase and sorbitol dehydrogenase. Ful pretreatment (225 mg.kg-1, sc x 3 d) decreased hepatic cytochrome P-450, cytochrome b5, and NADPH-cytochrome c reductase by approximately 15-20%. Microsomes from Ful-pretreated mice, incubated in vitro with AA, produced less AA-glutathione. A 28% increase in urinary excretion of AA-glucuronide was observed in Ful (150 mg.kg-1, sc x 3 d) pretreated mice. Ful pretreatment had no influence on liver UDP-glucuronic acid concentration, but increased hepatic glucuronyltransferase activity towards AA. In summary, Ful pretreatment protects against AA-induced hepatotoxicity. One of the mechanisms for this protection appears to be the decreased AA toxic activation via P-450, as well as increased detoxication via glucuronidation of AA.